Faktor-Faktor yang Berhubungan dengan Kelelahan Kerja pada Petugas Pengamanan Lingkungan Pelabuhan Ferry Mulia Raja Napitupulu Kota Balige (Inovasi Kesehatan Global, 2026)
Work fatigue is one of the occupational health problems that may affect productivity, concentration, and increase the risk of workplace accidents. Security officers at Ferry Mulia Raja Napitupulu Port, Balige, are at high risk of experiencing fatigue due to shift work systems, physical and mental workload, and poor sleep quality. This study aims to identify factors associated with work fatigue among security officers. A quantitative method with a cross-sectional design was applied. The sample consisted of 45 security officers selected using total sampling technique. Data were collected through questionnaires on individual characteristics, nutritional status, sleep quality, workload, and environmental temperature, and analyzed using bivariate tests. The results revealed significant relationships between age, nutritional status, sleep quality, workload, and temperature with work fatigue levels (p<0.05). It can be concluded that both individual and work environment factors contribute to fatigue among security officers. The study recommends that port management pay more attention to shift arrangements, rest patterns, and occupational health interventions to reduce fatigue risk and enhance officers’ productivity.